Analisis Sistem Penilaian Kinerja Karyawan pada PT X - Nasywa Aqilla Maheswari; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to analyze the employee performance appraisal system at PT X, a company engaged in shipping operators, ship ownership, and shipping agencies. The research method used is descriptive qualitative with a case study approach supported by data collection through observation, interviews, and documentation. The results showed that the performance appraisal system at PT X still faces obstacles in its implementation, where the majority of employees do not understand the system implemented, consider the system not objective and fair, and feel that the system has not been effective in improving work performance. The main obstacles identified include the lack of transparency of assessment criteria, subjectivity in the evaluation process, and the lack of constructive feedback to employees. Based on the findings, several solutions are recommended to overcome the obstacles in PT X's employee performance appraisal system, including the development of more structured and transparent appraisal criteria, implementation of a Key Performance Indicator (KPI)-based appraisal system, evaluator training to reduce bias in appraisal, and implementation of a comprehensive and regular feedback mechanism. The results of this study are expected to contribute to the company in developing a more effective performance appraisal system.